Popularisation by Argentine researchers: the activities and motivations of CONICET scientists - Jensen, Pablo (2011)
Fil: Levin, Luciano G. Universidad Maimónides. Centro de Ciencia, Tecnología y Sociedad. Buenos Aires; Argentina